Reconsidering Boccaccio : Medieval Contexts and Global Intertexts - Stortz, Diane, 1950-; Holmes, Olivia (Book collections on Project MUSE., 2018)
Reconsidering Boccaccio explores the exceptional social, geographic, and intellectual range of the Florentine writer Giovanni Boccaccio, his dialogue with voices and traditions that surrounded him, and the way that his legacy illuminates the interconnectivity of numerous cultural networks.